2016
DOI: 10.1007/s00265-016-2131-1
|View full text |Cite|
|
Sign up to set email alerts
|

Personality traits are consistent when measured in the field and in the laboratory in African striped mice (Rhabdomys pumilio)

Abstract: International audiencePersonality in free-living individuals has predominantly been measured under standardized laboratory conditions. Such measurements have been then linked to life-history traits, fitness and survival. Yet, it remains unclear how such personality measurements reflect the variation shown by free-living individuals, if the same measurements were taken directly in their natural environment. Here, we used free-living African striped mice to test whether the personality traits of activity, boldne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 67 publications
2
24
0
Order By: Relevance
“…These laboratory assays were used to assess the resemblance of parent and offspring colonies in a common garden environment. Although we might expect behaviour in the laboratory to differ substantially from that in the field due to the lack of all natural cues (but see: Boon, Réale, & Boutin, 2008;Fisher, James, Rodriguez-Munoz, & Tregenza, 2015;Herborn et al, 2010;Yuen, Pillay, Heinrichs, Schoepf, & Schradin, 2016), we might still expect the ranking of colonies in terms of their foraging aggression to be similar in both the laboratory and in the field. In this case, a positive correlation would be expected.…”
Section: Data Collectionmentioning
confidence: 99%
“…These laboratory assays were used to assess the resemblance of parent and offspring colonies in a common garden environment. Although we might expect behaviour in the laboratory to differ substantially from that in the field due to the lack of all natural cues (but see: Boon, Réale, & Boutin, 2008;Fisher, James, Rodriguez-Munoz, & Tregenza, 2015;Herborn et al, 2010;Yuen, Pillay, Heinrichs, Schoepf, & Schradin, 2016), we might still expect the ranking of colonies in terms of their foraging aggression to be similar in both the laboratory and in the field. In this case, a positive correlation would be expected.…”
Section: Data Collectionmentioning
confidence: 99%
“…Studies investigating behaviour of wild rodents have used tests adapted from these standardised tests to study the interaction between personality traits and ecological characteristics (Boon, Reale, & Boutin, ; Herde & Eccard, ; Yuen, Pillay, Heinrichs, Schoepf, & Schradin, , ). Common voles ( Microtus arvalis ) were for example found to exhibit seasonal differences in activity, measured as number of movements and number of barrier crosses and boldness, measured as latency to move and cross a barrier in an open field and a barrier crossing test (Herde & Eccard, ).…”
Section: Introductionmentioning
confidence: 99%
“…The different interpretations of the behaviours measured in supposedly the same situation such as an open field test can have a number of reasons. Two possible explanations that are currently discussed in the field relate to how individuals of different species or populations experience the situation (Carter, Feeny, Marshall, Cowlishaw, & Heinsohn, ) and the validity of measurements from standardised laboratory test setups to reflect natural behaviour (Arvidsson, Adriaensen, Dongen, Stobbeleere, & Matthysen, Lecorps, Kappel, Weary, & Keyserlingk, ; Yuen, Pillay, Heinrichs, Schoepf, & Schradin, ). Related to the first argument, one might for example argue that an open field should be a more stressful situation for species or populations which are predated on open ground while it should be less stressful for species/populations which main predators use different hunting strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetically polymorphism is maintained because of "supergenes", linked clusters of coevolved genes that give rise to divergent fitness-related traits that are variable within species (Schwander et al 2014;Tuttle et al 2016). Hence, while personality researchers would have been satisfied with identifying behavioral differences (e.g., Malange et al 2016;Michelangeli et al 2016;Yuen et al 2016), the fields of life-history evolution and behavioral genetics allows us to understand why individuals differ in their behavior. This is just one of many examples of studies that have identified the genetic mechanisms underlying animal behavior.…”
Section: Behavioral Genetics and Behavioral Neuroendocrinology: Undermentioning
confidence: 99%